2000
DOI: 10.1021/ol0061586
|View full text |Cite
|
Sign up to set email alerts
|

Non-Sonogashira-Type Palladium-Catalyzed Coupling Reactions of Terminal Alkynes Assisted by Silver(I) Oxide or Tetrabutylammonium Fluoride

Abstract: Palladium-catalyzed reaction of aryl and alkenyl halides with terminal alkynes in the presence of silver(I) oxide as an activator furnishes various arylated or alkenylated alkynes in good to excellent yields. The similar coupling reaction is also found to proceed using tetrabutylammonium fluoride (TBAF) or tetrabutylammonium hydroxide (TBAOH) as an activator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(79 citation statements)
references
References 15 publications
0
78
0
1
Order By: Relevance
“…[9] On the other hand, Herrmann and co-workers have recently found that the catalytic system Pd 2 (dba) 3 /P(t-Bu) 3 promotes the copper-free Sonogashira-type reaction of aryl bromides at room temperature. [10] Likewise, stoichiometric amounts of silver(I) oxide for aryl iodides, and tetrabutylammonium fluoride (Bu 4 NF) or tetrabutylammonium hydroxide (Bu 4 NOH) for aryl bromides, have also been used as activators in the first described copper-and amine-free procedure, [11] even though when using the ammonium salts as activators, the coupling reaction is rather sluggish and CuI has to be added in a further improved procedure. [12] With respect to the use of palladacycles [13] as pre-catalysts for the copper-free Sonogashira-type reaction, Herrmann×s phosphapalladacycle 2 [14] and carbene-derived palladacycles 3 [15] and 4 [16] (Figure 1), have been used in a copper-free protocol employing triethylamine (TEA) as solvent at 90 8C with turnover numbers (TON) of up to 8000 when using catalyst 2.…”
Section: Introductionmentioning
confidence: 99%
“…[9] On the other hand, Herrmann and co-workers have recently found that the catalytic system Pd 2 (dba) 3 /P(t-Bu) 3 promotes the copper-free Sonogashira-type reaction of aryl bromides at room temperature. [10] Likewise, stoichiometric amounts of silver(I) oxide for aryl iodides, and tetrabutylammonium fluoride (Bu 4 NF) or tetrabutylammonium hydroxide (Bu 4 NOH) for aryl bromides, have also been used as activators in the first described copper-and amine-free procedure, [11] even though when using the ammonium salts as activators, the coupling reaction is rather sluggish and CuI has to be added in a further improved procedure. [12] With respect to the use of palladacycles [13] as pre-catalysts for the copper-free Sonogashira-type reaction, Herrmann×s phosphapalladacycle 2 [14] and carbene-derived palladacycles 3 [15] and 4 [16] (Figure 1), have been used in a copper-free protocol employing triethylamine (TEA) as solvent at 90 8C with turnover numbers (TON) of up to 8000 when using catalyst 2.…”
Section: Introductionmentioning
confidence: 99%
“…24 In this report several aryl and alkenyl halides were successfully cross-coupled in good to excellent yields with terminal alkynes in the presence of silver(I) oxide, tetrabutylammonium fluoride (TBAF) or tetrabutylammonium hydroxide (TBAOH) as activators. Intrigued by this finding we set up several palladium-catalyzed crosscoupling attempts with […”
Section: Resultsmentioning
confidence: 99%
“…[106,152,160] Auf der Grundlage ihrer nickelkatalysierten Reaktion von Kupferacetyliden mit 4 Ein äußerst innovativer Ansatz zur metallfreien Alkinylierung von Arylvorstufen geht auf Fagnoni und Albini zurück. [162] Sie untersuchten die Photolyse verschiedener Vorstufen des 4-Methoxyphenylkations (das entsprechende Arylchlorid, -fluorid, -mesylat, -triflat sowie -diethylphosphat) in Gegenwart von 10 ¾quivalenten des terminalen Abschließend ist erwähnenswert, dass Silberoxid [163] und Indiumtribromid [164] als stöchiometrisches Reagens bzw. katalytischer Promotor bei der kupferfreien palladiumkatalysierten Alkinylierung von Aryliodiden eingesetzt wurden.…”
Section: Arylsubstratunclassified